Intelligent Information Technology-based ICT Education and Creativity Education Develop Core Competencies - Jung, Yujin; Park, Namje (International Journal of Advanced Science and Technology, 2019)
Background/Objectives: For the prosperity in the 21st century that is evolving rapidly, students need more than what they have learned. In the future society, students must get used to cease-less cooperation, communication and problem solving, and it can be developed through social and emotional learning(SEL).Methods/Statistical analysis: This paper investigates today’s teaching of creativity and the importance of school teachers in such teaching and accordingly proposes a new model for training the teachers on creativity-teaching.Findings: Intelligent Information Technology is applied to a wide range of industries such as intelligent robotics, smart manufacturing and blockchain, and is giving rise to massive innovation in economy and society as a whole.Improvements/Applications: Viewed in the context of such significance, ICT competencies and IIT are the subjects that should henceforth be addressed with importance in school education.